2022
DOI: 10.1093/g3journal/jkac023
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas CHT7 is involved in repressing DNA replication and mitotic genes during synchronous growth

Abstract: In the green alga Chlamydomonas reinhardtii, regulation of the cell cycle in response to external cues is critical for survival in a changing environment. The loss of the nuclear COMPROMISED HYDROLYSIS OF TRIACYLGLYCEROLS 7 (CHT7) protein affects the expression of many genes especially in response to nitrogen availability. Cells lacking CHT7 exhibit abnormal cell morphology following nitrogen deprivation (ND) and fail to resume normal cell division after N resupply. To investigate the function of CHT7 in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…P -values obtained from DESeq2 were adjusted for multiple testing using Bejamini-Hochberg correction to control for false discovery rates. Gene ontology (GO) enrichment analysis using the R package topGO 2.40.0 (Alexa et al 2006) and the GO annotation table from (Lin et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…P -values obtained from DESeq2 were adjusted for multiple testing using Bejamini-Hochberg correction to control for false discovery rates. Gene ontology (GO) enrichment analysis using the R package topGO 2.40.0 (Alexa et al 2006) and the GO annotation table from (Lin et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, on nutrient replenishment (NR), these cells exit quiescence, utilize the accumulated TAG as an initial burst of energy and restart its growth and division activities (3, 6). Extensive work by Benning and coauthors have shown that the entry and exit from quiescence is regulated through a protein called Compromised Hydrolysis of Triacylglycerol 7 (CHT7) (3, 7, 8). Efficient entry into the quiescence and maintenance of this state are necessary for a successful exit from the quiescence (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…There is still much to learn about how these common organisms function. Well-done studies on single genes that advance the field always have a home in G3 , and we’ve also seen targeted high-throughput approaches to comprehensively identify new functions or pathways involving known factors ( Lao et al 2018 ; Chatfield-Reed et al 2022 ; Lin et al 2022 ; Li et al 2024 ).…”
mentioning
confidence: 99%